BLENDED LEARNING AND EXTENSIVE LISTENING: A PROMISING COLLABORATION TO ENHANCE LISTENING SKILL - Fitri Awaliyatush Sholihah; Mukhamad Bayu Permadi; Atik - Umamah (IAIN Syekh Nurjati Cirebon, 2018)
This research aimed at describing how blended learning strategy by integrating portfolio-based extensive listening activity can improve studentsâ€™ listening skill. This action research was the response of the classroom problem identified in Listening 2 course in class 2E of English Department, Universitas Islam Malang. The problem was the average score of this class was low (68.86) and only 45% of the students achieved the standard minimum score (â‰¥ 75). Data from interview uncovered that the major cause was insufficient exposure to authentic listening input. The instruments used to gain the data were portfolio and test. The criterion of success set was that 70% of the students obtained the standard minimum score. This research was conducted in two cycles with four meetings for each. At the end of cycle 1, the average score was 75.36 but only 55% of the students achieved the standard minimum score. The test result in cycle 2 indicated that the average score was 78.36 and 73% of the students reached the standard minimum score, meaning that the criterion of success was achieved. This implies that the implementation of blended learning approach with portfolio-based extensive listening activity can significantly enhance listening skill.